(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Using outputs of INDESO model, this study investigated vertical structure, spatial and temporal variation of the Indonesian Throughflow in Makassar Strait (M-ITF). It was shown that the main axis of persistent southward jet of M-ITF formed a unique path following the western shelf slope along the strait, which was associated with a high kinetic energy (KE) region from near-surface down to the thermocline layer. Furthermore, a drastic jump of KE appeared in the narrow and deep Libani Chan-nel (near 3°S) where the strait’s width shrinks significantly, thus an elevated flow velocity was needed to maintain transport volume balance. Here, maximum southward velocity at thermocline exceeded 1.2 m/s. Spatial pattern of M-ITF can be described by the first EOF mode which accounts for 79 % of the total variances. It exhibited that contours of the flow amplitudes were similar to M-ITF path, and the largest amplitude was located near the Libani Channel. Out-of-phase relationship of the flow was found between M-ITF and eddies circulation that developed in the edges of the strait. Corresponding temporal fluctuation of the first EOF mode indicated that M-ITF variabilities varied from intra-seasonal to inter-annual scales. Annual fluctuation of M-ITF was seen from EOF mode-2 (at thermocline layer) and mode-3 at lower-thermocline. Cross-spectra analysis revealed that variability of M- ITF (e.g. on annual scale) at northern entrance was highly coherent to the fluctuations of North Equatorial Current (NEC) and Mindanao Current (MC), suggesting that variability of M-ITF was remotely influenced by the Pacific low-latitude western boundary currents. Keywords: INDESO model, Indonesian Throughflow, Makassar Strait, EOF, Cross-Spectra Analysis